Gradient rhenium doping enabled tunable anisotropic valleytronic material based on monolayer molybdenum disulfide. (5th May 2021) - Ma, Xinli; Zhang, Jing; Lai, Jiawei; Zhang, Mingwen; Zheng, Jingchuan; Wu, Sen; Hu, Xiaodong; Wang, Qinsheng; Gan, Xuetao; Sun, Dong; Liu, Jing
Abstract: Two-dimensional molybdenum disulfide (MoS2 ) possesses premium electrical, optoelectrical and valleytronic properties to develop future nano-electronic and optoelectronic devices. Valleytronic material platform with anisotropic response is highly desired to develop polarization sensitive valleytronic devices. In this work, we acquire monolayer MoS2 with both valley degree of freedom and anisotropy by introducing Re doping during chemical vapor deposition growth. The atomic substitution with Re element induces prominent n-type doping. Electrical tests under both dark and light illumination show that 5 at% Re-doped MoS2 achieves the optimum electrical and optoelectrical performances, corresponding to 27 and 35 times improved carrier mobility and photoresponsivity than pristine MoS2, respectively. Second harmonic generation (SHG) and polarization Raman spectroscopy (PRS) indicate increased anisotropic optical response of Re doped MoS2 as Re concentration increases: maximum anisotropic ratios of 1.6 and 1.7 have been achieved for SHG and PRS measurements at different doping concentrations, respectively. Circularly polarized PL measurement demonstrates that the Re-doped MoS2 preserves valley dependent optical response. Our theoretical calculations show that the anisotropic response is due to the strain induced by the dopants, so that the 2H lattice structure optical helicity dependent valley selection rules are largely preserved. The work opens promising venue toward polarization sensitive valleytronic material platform.